In vivo standardization of bone ultrasonometry of the clavicle - Luiz Garcia Mandarano-Filho; Márcio Takey Bezuti; Cláudio Henrique Barbieri (Clinics, 2016)
OBJECTIVE: The assessment of fracture union includes physical examination and radiographic imaging, which depend on the examiner’s experience. The development of ancillary methods may avoid prolonged treatments and the improper removal of implants. Quantitative bone ultrasonometry has been studied for this purpose and will soon be included in clinical practice. The aims of the present study were to assess the feasibility of using this technique on the clavicle and to standardize its in vivo application. METHODS: Twenty adult volunteers, including 10 men and 10 women without medical conditions or a previous history of clavicle fracture, underwent axial quantitative ultrasonometric assessment using transducers in various positions (different distances between the transducers and different angulations relative to the clavicle). RESULTS: Similar values of wave propagation velocity were obtained in the different tested set-ups, which included distinct distances between the transducers and angular positions relative to the clavicle. There were significant differences only in the transducers positioned at 0° and at 5 or 7 cm apart. CONCLUSIONS: The use of bone ultrasonometry on the clavicle is feasible and the standardization of the technique proposed in this study (transducers placed at 45° and at 7 cm apart) will allow its future application in clinical trials to evaluate the healing process of diaphyseal fractures of the clavicle.